Thermodynamic Properties of $Zr_2Al$ Under High Pressure from First-Principles Calculations (Journal of Atomic and Molecular Sciences, 2021)
The equations of state (EOS) and other thermodynamic properties of hcp structure $Zr_2Al$ are studied using first-principles calculations based on the plane wave pseudopotential density functional theory method within the generalized gradient approximation (GGA) for exchange and correlation. It is demonstrated that the ratio $c/a$ of about 1.208 is the most stable structure for the hcp $Zr_2Al,$ which is consistent with the experimental data. Through the quasi-harmonic Debye model, in which the phononic effects are considered, the dependences of relative volume $V/V_0$ on pressure $P,$ cell volume $V$ on temperature $T$ are successfully obtained. The variations of the Debye temperature $Θ,$ the thermal expansion a , the Grüneisen parameter $γ$ and the heat capacity $C_v$ with pressure $P$ and temperature $T$ are investigated systematically in the ranges of 0-100 GPa and 0-1500 K.